2003
DOI: 10.1016/s0168-6445(03)00050-0
|View full text |Cite
|
Sign up to set email alerts
|

Zn, Cu and Co in cyanobacteria: selective control of metal availability

Abstract: Homeostatic systems for essential and non-essential metals create the cellular environments in which the correct metals are acquired by metalloproteins while the incorrect ones are somehow avoided. Cyanobacteria have metal requirements often absent from other bacteria; copper in thylakoidal plastocyanin, zinc in carboxysomal carbonic anhydrase, cobalt in cobalamin but magnesium in chlorophyll, molybdenum in heterocystous nitrogenase, manganese in thylakoidal water-splitting oxygen-evolving complex. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
151
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(159 citation statements)
references
References 114 publications
6
151
0
2
Order By: Relevance
“…The results of the BEST analysis indicated that differences in soil elemental composition may be a contributing factor. Research on a variety of cyanobacterial species has shown that they have metal ion requirements often absent from other bacteria (Cavet et al, 2003) and that depauparate concentrations of some elements limit cyanobacterial growth. For example, oceanic cyanobacterial growth has been shown to be limited by iron, possibly due to its requirement in nitrogenase and hence nitrogen fixation (Chisholm et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the BEST analysis indicated that differences in soil elemental composition may be a contributing factor. Research on a variety of cyanobacterial species has shown that they have metal ion requirements often absent from other bacteria (Cavet et al, 2003) and that depauparate concentrations of some elements limit cyanobacterial growth. For example, oceanic cyanobacterial growth has been shown to be limited by iron, possibly due to its requirement in nitrogenase and hence nitrogen fixation (Chisholm et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of two of these, magnesium and manganese, were significantly lower in the Beacon Valley than in the Miers Valley samples. Both of these elements are involved in key cellular processes in cyanobacteria, magnesium in chlorophyll production (Cavet et al, 2003) and manganese in the thylakoidal water-splitting oxygen-evolving complex (Bartsevich and Pakrasi, 1996). Some metals have also been shown to have a toxic effect on cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Effective metal-ion homeostasis requires the balanced activity of metal-ion-uptake, efflux, sequestration and redox systems (Solioz & Stoyanov, 2003;Rensing & Grass, 2003;Cavet et al, 2003). So far, our screening of the Ferroplasma genome sequences has failed to reveal the presence of other copper transport mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, tightly controlled homeostatic systems need to permit delivery of the metal to specific target enzymes, while maintaining low intracellular concentrations of free ionic Cu + . It is likely that most, if not all, organisms have mechanisms for copper homeostasis (Rensing et al, 2000), and this has been studied in certain bacteria that include Enterococcus hirae (Solioz & Stoyanov, 2003), Escherichia coli (Rensing & Grass, 2003) and cyanobacteria (Cavet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…D uring the last few years, an increasing number of genes have been discovered to be implicated in many intracellular pathways of metal trafficking (1)(2)(3)(4). Some of these genes are conserved in all organisms, whereas others are present in prokaryotic or eukaryotic organisms only.…”
mentioning
confidence: 99%